2013
DOI: 10.1016/j.biopsycho.2013.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Fearless Dominance and reduced feedback-related negativity amplitudes in a time-estimation task – Further neuroscientific evidence for dual-process models of psychopathy

Abstract: HighlightsDual-process models of psychopathy postulate two underlying dimensions.Fearless Dominance was associated with altered feedback processing.Feedback-related negativity amplitudes were reduced.Self-Centered Impulsivity was unrelated to feedback processing.These findings provide further evidence for dual-process models of psychopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 102 publications
(82 reference statements)
3
17
1
Order By: Relevance
“…This was not seen, as individuals with antisocial traits failed to show a FRN in response to suboptimal outcomes in both social and non-social contexts. This is consistent with a recent study finding reduced FRN amplitudes to both social and non-social feedback in typically developing individuals with high levels of psychopathic traits, although this study found associations with the ‘fearless dominance’ aspect of psychopathy, rather than the antisocial dimension (Schulreich et al, 2013). This lack of sensitivity to feedback could underlie the preponderance of impulsively aggressive acts associated with antisocial traits, as cues to inhibit inappropriate behaviors may be insufficiently salient to modulate behavior.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This was not seen, as individuals with antisocial traits failed to show a FRN in response to suboptimal outcomes in both social and non-social contexts. This is consistent with a recent study finding reduced FRN amplitudes to both social and non-social feedback in typically developing individuals with high levels of psychopathic traits, although this study found associations with the ‘fearless dominance’ aspect of psychopathy, rather than the antisocial dimension (Schulreich et al, 2013). This lack of sensitivity to feedback could underlie the preponderance of impulsively aggressive acts associated with antisocial traits, as cues to inhibit inappropriate behaviors may be insufficiently salient to modulate behavior.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically regarding the FRN component, individuals with higher scores on the ‘fearless dominance’ aspect of psychopathic traits (characterized by impairments in interpersonal sensitivity) show reduced FRN amplitudes to negative feedback (Schulreich, Pfabigan, Derntl & Sailer, 2013). Individuals scoring higher on questionnaires of antisocial personality show decreased FRN response to social, as compared to non-social, feedback (Pfabigan, Alexopoulos, Bauer, Lamm, & Sailer, 2011).…”
mentioning
confidence: 99%
“…The influence of personal distress on JSSelf also seems consistent with the work in personality psychology indicating that individuals scoring high on fearless dominance exhibit low trait anxiety, as well as aspects of positive adjustment, such as sociability and well-being (Benning et al, 2005). Fearless dominance, which encompasses the emotional-interpersonal aspects of psychopathy and is related to an arrogant interpersonal style, lack of empathy and reduced fear reactivity, is associated with alteration in feedback processing, including feedback-related negativity amplitudes measures with EEG, whose sources originate in the anterior cingulate cortex (Schulreich et al, 2013). Such a deficiency in processing feedback may contribute to reduced sensitivity to justice when the recipient if the self, perhaps because these individuals are relatively immune to the anxiety and fear associated with the experience injustice.…”
Section: Discussionmentioning
confidence: 99%
“…Psychopathic personality traits vary along a continuum which extends into the general population, and include a lack of empathy, callous disregard for the wellbeing of others, and lack of concern about moral wrongdoing (Maibom, 2009; Seara-Cardoso & Viding, 2014; Skeem, Polaschek, Patrick, & Lilienfeld, 2011). These traits can be clustered into three high-level factors (Benning, Patrick, Blonigen, Hicks, & Iacono, 2005), which differentially influence behavior, attention, and cognition (Larson et al, 2013; Sadeh & Verona, 2008; Schulreich, Pfabigan, Derntl, & Sailer, 2013). In particular, results from behavioral and neuroimaging studies demonstrate that psychopaths, from forensic and non-forensic samples, are impaired in their capacity to experience empathic concern (Decety, Chen, Harenski, & Kiehl, 2013, 2015; Rosas & Koenigs, 2014; Sobhani & Bechara, 2011; Yoder, Porges, & Decety, 2015), and this lack of concern for others affects their decision-making and moral behavior (Decety & Cowell, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…personality, temperament, anti-social behaviour, and social functioning) (Benning et al, 2003;Harpur, Hare, & Hakstian, 1989;Hicks et al, 2004). A recent study also found differences between primary and secondary psychopathy in feedbackrelated negativity (FRN) for positive and negative faces on a time estimation task, with primary, but not secondary psychopathy, related to reduced FRN (Schulreich, Pfabigan, Derntl, & Sailer, 2013). A further extension of the dual process model is the Triarchic Model of Psychopathy, which seeks to address the discrepancies in the conceptualization of psychopathy between criminal and noncriminal classifications ).…”
Section: Successful Psychopathymentioning
confidence: 99%